A case report of hypospadias combined with polyorchidism - Wentao Yu; Wei Gong; Fuhan Zhao; Guan Zhang; Zhenyu Liu; Tiejun Pan (Urology Case Reports)
Hypospadias is a common congenital malformation of the reproductive system; however, to date, no cases of hypospadias complicated by polyorchidism have been reported in the literature. This article reports a case of a 1-year-old boy presenting with hypospadias, who was also diagnosed with polyorchidism combined with cryptorchidism. Preoperative Doppler ultrasound revealed two testes on the right side, and an atrophic testis on the left. After surgical treatment, the patient recovered well and was discharged. Hypospadias combined with polyorchidism is highly prone to misdiagnosis or missed diagnoses. This case provides insight into the recognition, diagnosis, and treatment of this condition.